Evaluation of the influence of vertical irregularities on the seismic performance of a nine-storey steel frame. - Michalis, Fragiadakis
A methodology based on incremental dynamic analysis (IDA) is presented for the evaluation of structures with vertical irregularities. Four types of storey-irregularities are considered: stiffness, strength, combined stiffness and strength, and mass irregularities. Using the well-known nine-storey LA9 steel frame as a base, the objective is to quantify the effect of irregularities, both for individual and for combinations of stories, on its response. In this context a rational methodology for comparing the seismic performance of different structural configurations is proposed by means of IDA. This entails performing non-linear time history analyses for a suite of ground motion records scaled to several intensity levels and suitably interpolating the results to calculate capacities for a number of limit-states, from elasticity to final global instability. By expressing all limit-state capacities with a common intensity measure, the reference and each modified structure can be naturally compared without needing to have the same period or yield base shear. Using the bootstrap method to construct appropriate confidence intervals, it becomes possible to isolate the effect of irregularities from the record-to-record variability. Thus, the proposed methodology enables a full-range performance evaluation using a highly accurate analysis method that pinpoints the effect of any source of irregularity for each limit-state.
Keywords: Incremental dynamic analysis; Vertical irregularities; Non-linear dynamic analysis; Seismic performance evaluation; Bootstrap